La dynamique de construction du jugement évaluatif du superviseur lors de l’évaluation de stages en enseignement - Maes, Olivier; Van Nieuwenhoven, Catherine; Colognesi, Stéphane (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
In the context of initial teacher training courses, and more particularly in the Frenchspeaking part of Belgium, this contribution attempts to answer the question: how to characterize the construction of the supervisor’s evaluative judgment during the co-assessment interview? To answer this question, we conducted an exploratory study. This is a multicase study based on two co-evaluation interviews conducted by two supervisors from the same training institute. The results show that the process is dynamic and iterative, taking into account a series of partial and provisional judgments in order to construct the final evaluative judgment that meets the characteristics of professional judgment in evaluation. Keywords: traineeship, supervisor, co-assessment, professional judgment in evaluation